Contrived motivating operations alter delay‐discounting values of disordered gamblers. Issue 4 (11th July 2016) - Dixon, Mark R.; Buono, Frank D.; Belisle, Jordan
Abstract : The present study required 9 disordered gamblers to make hypothetical selections between smaller and larger amounts of money at varying delays. Participants were also required to respond to the task given the contrived hypothetical conditions of earning twice or half as much as they did at their current jobs. The results demonstrated how participants' delay discounting was altered via contrived motivating operations, strengthening the argument that discounting may be a state variable.